Forschungsschwerpunkte und Zukunftsaufgaben der Historischen Geographie: Verkehr - Schäfer, Hans-Peter (ERDKUNDE, 1982)
Within German historical geography there exists a section that specifically concerns the communications network and traffic and transport in the historical landscape (Altlandschaft). Scientific research, which reached a high peak with F. Rauers in 1906 (until today his detailed map of the late-medieval commercial transportation network in Central Europe remains the only one!) is carried out as much to discover network connections within an historical landscape and between ancient settlements (see Denecke 1969) as to study the development and significance of historical transportation networks for themselves (spatial persistence of a network frame through the circumstances of the old German law; see Schafer 1976 and 1979) or their importance for historic landscape development. By this means German “Historische Verkehrsgeographie...? and approaches political relations (historical network research) as well as economic space questions (location of industries and settlement). Nowadays the „Langsschnitt-Analyse (temporal transect analysis) could and should help to give better-based trend analyses for network planning, since geography allows individual and complex space knowledge.